Anaesthetic management and complications of pacemaker implantation in dogs. (27th September 2014) - Sanchis‐Mora, S.; Viscasillas, J.; Mathis, A.; Palacios, C.; Brodbelt, D. C.; Alibhai, H. I.
Abstract : The aim of this study was to report the anaesthetic management and peri‐anaesthetic complications of 57 dogs undergoing pacemaker implantation at a referral institution over 10 years (2002–2012). The median duration of the procedure was 135 minutes (range 25–260 minutes). Patients were classified as American Society of Anaesthesiologist (ASA) III (42 cases) and ASA IV (15 cases). Forty‐three patients had third‐degree atrioventricular block, and 14 patients had sick sinus syndrome. The anaesthetic protocol most frequently chosen was pethidine (41 cases), etomidate‐midazolam (43 cases) and isoflurane in oxygen for maintenance (57 cases). Transthoracic external pacing was used (43 cases) until the internal pacing lead was implanted. Atracurium was administered (48 cases) and intermittent positive pressure ventilation was applied in 52 cases. Complications observed included hypothermia (19 cases) and hypotension (5 cases). Three patients died (5.8%, 95% CI 1.1% to 14.6%) within the first 48 hours after termination of anaesthesia. The outcome for this procedure in sick animals appeared generally good though a number of complications were documented.